Cytogenetically distinguishable sympatric and allopatric populations of the mosquito Anopheles albitarsis - R. D. Kreutzer; J. B. Kitzmiller; M. G. Rabbani (Acta Amazonica, 1976)
Abstract Salivary gland chromosome slides of Anopheles albitarsis from Brasil, Colombia and Venezuela indicate that at least three chromosomally differentiated populations of this species exist in this area. The B1 population from Brasil contains one heterozygous inversion in the X and two in the autosomes. Population B2, sympatric with B1 in Brasil, differs from it by two inversions in the X and ten in the autosomes. Population C in Colombia and Venezuela is closer to B1, from which it differs by three inversions in chromosome 2 and three in chromosome 3. Each population, B1, B2 and C may be distinguished with about 98% certainty using the banding patterns of the X chromosomes. Most of the remaining individuals may be identified using a combination of the X and autosomal paracentric inversions. The scarcity of shared inversions argues for little if any natural hybridization among these populations. A standard salivary gland chromosome map, based on the B1 populations, is presented.